Sustainability and scalability of university spinouts: a business model perspective. (25th September 2015) - Ziaee Bigdeli, Ali; Li, Feng; Shi, Xiaohui
Abstract : Most previous studies of university spinouts (USOs) have focused on what determines their formation from the perspectives of the entrepreneurs or of their parent universities. However, few studies have investigated how these entrepreneurial businesses actually grow and how their business models evolve in the process. This paper examines the evolution of USOs' business models over their different development phases. Using empirical evidence gathered from three comprehensive case studies, we explore how USOs' business models evolve over time, and the implications for the financial sustainability and operational scalability of these ventures. This paper extends existing research on the development of USOs, and highlights three themes for future research.